PENGENDALIAN JARINGAN DISTRIBUSI 20 KV DENGAN MENGGUNAKAN SISTEM SCADA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
In Indonesia, especially at PT PLN (Persero), SCADA has been known and started to be implemented in the control of electric power systems since the early 1980s in many other countries that are more advanced, SCADA application is growing in line with the development of computer technology and telecommunications. By the time the development is not as sophisticated SCADA now, there are thought to facilitate maneuvers on a system that is simple to use SCADA network we can supply additional power or power outage easily do so overloaded that did not happen. After implementing a SCADA system occurred saving time for 2906 minutes or 48.44 hours, and the frequency of outages 4 times less than that before implementing the SCADA system. This means that the reliability index SAIDI and SAIFI much better at the moment after the implementation of the SCADA system.